1992
DOI: 10.1104/pp.98.1.246
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Root Elongation and Curvature by Calcium

Abstract: Ca2+ has been proposed to mediate inhibition of root elongation. However, exogenous Ca2+ at 10 or 20 millimolar, applied directly to the root cap, significantly stimulated root elongation in pea (Pisum sativum L.) and com (Zea mays L.) seedlings. Furthermore, Ca2+ at 1 to 20 millimolar, applied unilaterally to the caps of Alaska pea roots, caused root curvature away from the Ca2+ source, which was caused by an acceleration of elongation growth on the convex side (Ca2+ side) of the roots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 21 publications
3
20
1
Order By: Relevance
“…Takahashi et al (24) reported effects of Ca opposite to ours. They found that application of Ca to the cap stimulated elongation and that unilateral application induced negative curvature by accelerating elongation on the side to which Ca was applied.…”
Section: Plant Materialscontrasting
confidence: 81%
“…Takahashi et al (24) reported effects of Ca opposite to ours. They found that application of Ca to the cap stimulated elongation and that unilateral application induced negative curvature by accelerating elongation on the side to which Ca was applied.…”
Section: Plant Materialscontrasting
confidence: 81%
“…The requirement for calcium in the ethylene-based triple response proved to be complex because normal hypocotyl elongation required the presence of calcium. Calcium has been shown to be stimulatory to root elongation in pea and corn as well (Takahashi et al, 1992). Interestingly, analysis of Arabidopsis mutants insensitive to ethylene (ein) or that lack the ability to form hooks (his) suggests that hypocotyl hook formation and elongation of hypocotyl and root are independent ethylene responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence has been indirect and sometimes contradictory. For example, unilateral application of Ca 2+ via agar blocks, which has often been cited as evidence for a role of Ca 2 + asymmetries in the root graviresponse, do not always lead to the same result (Hasenstein et al, 1988;Ishikawa and Evans, 1992;Takahashi et al, 1992). Ca 2< transport studies have shown the preferential polar transport of 45 Ca 2 ' toward the lower side of graviresponding maize roots (Lee et al, 1983b), but no asymmetry in free Ca 2+ between upper and lower sides of the roots could be detected (Dauwalder et al, 1985).…”
Section: Discussionmentioning
confidence: 99%